Cephalometric deviations present in children and adolescents with temporomandibular joint disorders - Leticia Vilaça Willeman Bastos; Ricardo de Souza Tesch; Odilon Victor Porto Denardin (Dental Press Editora, 2012)
INTRODUCTION: Temporomandibular disorders (TMD) have proved to be a risk factor for developing hyperdivergent facial growth patterns. OBJECTIVE: The aims of this study were: (1) Assess differences between the cephalometric measurements in children with articular TMD and a control group, before and after mandibular growth peak according to cervical vertebral maturation; and (2) Identify a predictive model capable of differentiating patients with TMD and control group patients based on early cephalometric characteristics. METHOD: The study included children and adolescents with maximum age of 17 years, divided into experimental group (n=30) diagnosed with articular TMD-according to the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) for children and adolescents-subdivided according to growth stage, called pre-peak (n=17) and post-peak (n=13) and control group (n = 30), matched by gender, skeletal maturity stage of the cervical vertebrae and classification of malocclusion. Lateral cephalometric and craniofacial structures were traced and their relations divided into: Cranial base, maxilla, mandible, intermaxillary relations, vertical skeletal relations and dental relations. Differences between the means for each variable were evaluated by applying the statistical Student t test for independent samples. RESULTS: The means of the variables analyzed in the pre-peak showed no statistically significant differences. However, analysis of post-peak showed that the experimental group displayed decreased SNA and SNB and increased SN.Gn and 1.NB (p<0.05). CONCLUSION: It was possible to identify a predictive model able to differentiate patients with TMD and asymptomatic controls from early cephalometric characteristics.